Research and Model Analysis on the Value of Integrating the Spirit of "Two Bombs and One Satellite" into Contemporary Ideological and Political Education Curriculum - Yang, Zenghui (Journal of Theory and Practice of Social Science, 2023)
The spirit of "Two Bombs and One Satellite" is a great representative spirit of the era in the early days of the founding of New China. It is a microcosm of the spirit of countless scientific researchers and the people during the socialist revolution and construction period, fearless of difficulties, united and dedicated, and has a high value of the times and a profound connotation of cultivating talents. Systematically studying the spirit of "Two Bombs and One Satellite" and introducing it into the "Trinity" ideological and political classrooms of universities, middle and primary schools, enriching the teaching content of ideological and political classrooms, improving the teaching methods of ideological and political classrooms, expanding students' understanding of ideological and political classrooms, increasing students' knowledge reserves, etc., strengthening the value analysis of ideological and political classrooms as a whole, guiding students to set lofty goals, cultivate patriotism, and improve personal ideological and moral literacy Tempering firm ideals and beliefs is of great significance and extraordinary value.